1994
DOI: 10.1046/j.1537-2995.1994.34194098595.x
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring transfusionist practices: a strategy for improving transfusion safety

Abstract: The QA/QI process described in this report, or one similar to it, could improve transfusion safety and serve as a model for increased involvement by transfusion service medical directors in the oversight of transfusionists' practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(26 citation statements)
references
References 5 publications
1
25
0
Order By: Relevance
“…Autologous blood products and the PABD procedure itself are subject to similar conditions as the homologous blood transfusion procedure: As analyzed in retrospective analyses [4][5][6][7], ABO-incompatible autologous transfusions due to clerical errors, occur in 1:5,000 to 1:31,000 transfusions. This rate of human errors is comparable to the mix-up rate found retrospectively in transfusion of homologous blood products (reviews in [8][9][10]). Transfusion to the wrong patient is therefore deemed likely to be the most important transfusion risk nowadays [9].…”
Section: Assumption 2: Pabd Prevents Transmission Of Viruses Via Bloosupporting
confidence: 66%
“…Autologous blood products and the PABD procedure itself are subject to similar conditions as the homologous blood transfusion procedure: As analyzed in retrospective analyses [4][5][6][7], ABO-incompatible autologous transfusions due to clerical errors, occur in 1:5,000 to 1:31,000 transfusions. This rate of human errors is comparable to the mix-up rate found retrospectively in transfusion of homologous blood products (reviews in [8][9][10]). Transfusion to the wrong patient is therefore deemed likely to be the most important transfusion risk nowadays [9].…”
Section: Assumption 2: Pabd Prevents Transmission Of Viruses Via Bloosupporting
confidence: 66%
“…Audit has been used to increase com pliance with procedures for bedside administration of blood products [27,28]. Shulman et al [27] found a high 50% noncompliance rate with blood administration policies in an initial audit. With feedback, education and repeat audits, the noncompliance rate fell to nearly zero.…”
Section: Audit Of Blood Administrationmentioning
confidence: 99%
“…Numerous studies have described patient misidentification detected by bedside control [1,10], and/or wristband check [2,11,12]. However, less attention has been given to identification errors involving namesake, i.e., name similarity issues [13,14], and impersonation, i.e., fraudulent identity documents.…”
Section: Introductionmentioning
confidence: 99%